2005
DOI: 10.1111/j.1745-4530.2005.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Moisture Loss From the Cooling Data of Potatoes

Abstract: A procedure was developed to predict moisture loss from cooling data of potato packed in gunny bags and stacked on wooden platforms in commercial cold stores. To predict the moisture loss, mass transfer coefficients k c and k m were estimated during the storage period, which were found to decrease with time. The calculated time average k c and k m values were 1.83 ¥ 10 -4 m/s and 2.31 ¥ 10 -10 kg/s·m 2 ·Pa during the transient cooling period and 1.59 ¥ 10 -4 m/s and 2.27 ¥ 10 -10 kg/s·m 2 ·Pa for the rest of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…In the regime of natural convection in porous media, van der Sman (1999) pointed out that the air temperature can be taken equal to the product temperature, i.e., T f = T p = T; and the heat transfer can be described by a single energy equation eliminating the need for additional heat transfer equation on product-air interface. Chourasia, Maji, Baskey, and Goswami (2005) also confirmed the above hypothesis experimentally and articulated that at any particular instant of time, the temperature difference between the product and air in the stack does not vary significantly. Hence, single energy equation was chosen for the present case to describe the heat transfer in the stack of potatoes (Beukema, Bruin, & Schenk, 1983).…”
Section: Energy Equationsupporting
confidence: 81%
See 1 more Smart Citation
“…In the regime of natural convection in porous media, van der Sman (1999) pointed out that the air temperature can be taken equal to the product temperature, i.e., T f = T p = T; and the heat transfer can be described by a single energy equation eliminating the need for additional heat transfer equation on product-air interface. Chourasia, Maji, Baskey, and Goswami (2005) also confirmed the above hypothesis experimentally and articulated that at any particular instant of time, the temperature difference between the product and air in the stack does not vary significantly. Hence, single energy equation was chosen for the present case to describe the heat transfer in the stack of potatoes (Beukema, Bruin, & Schenk, 1983).…”
Section: Energy Equationsupporting
confidence: 81%
“…where Y i is mass fraction of species 'i', S i is species source term, kg m À3 s À1 and was obtained from (Chourasia et al, 2005)…”
Section: Species Transport Equationmentioning
confidence: 99%
“…As little as a 3 to 10% loss in weight could have an adverse effect on the appearance, saleable weight, texture quality of fresh and FC produce (Ben-Yehoshua, 1987). In a related report, when RH of storage air for potatoes was decreased below 85%, more than 7% water loss was observed (Chourasia et al, 2005). Similarly, an increase in water loss during the ripe phase of ''Hass'' avocados was observed when the fruits where transferred from RH of 90 to 20%, Burdon et al (2005) reported a 30% increase in moisture loss when RH of stored apples was reduced from 97.5 to 95%.…”
Section: Transpiration Rate Of Pomegranate Arilsmentioning
confidence: 88%
“…Fresh produce such as fruit release large amounts of water vapour and without appropriate packaging, water vapour could build-up inside the package, facilitating the growth of microorganisms (Mahajan, Oliveira, & Macedo, 2008). Transpiration rate (TR) of produce during postharvest handling and storage is influenced by intrinsic factors such as surface-to-volume ratio, surface injuries, morphological and anatomical characteristics, as well as maturity stage (Sastry & Buffington, 1982), and extrinsic factors such as temperature, RH, air movement, and atmospheric pressure (Chourasia, Maji, Baskey, & Goswami, 2005). Pomegranate (Punica granatum L.) has been well documented for its potential health benefits such as its high antioxidant, anti-mutagenic, anti-hypertension, anti-inflammatory and anti-atherosclerotic activity against osteoarthritis, prostate cancer, heart disease and HIV-1 (Rı´os-Romero et al, 2012;Viuda-Martos, Ferna´ndez-Lo´pez, & Pe´rez-Á lvarez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The loss of moisture from the potato surface removes the latent heat of evaporation and produces the cooling effect. The rate of loss of moisture from the potato was calculated based on the procedure suggested by Chourasia et al . (2005):…”
Section: Methodsmentioning
confidence: 99%